Inside Cover: Quantum Influences in the Diffusive Motion of Pyrrole on Cu(111) (Angew. Chem. Int. Ed. 19/2013). Issue 19 (9th April 2013) - Lechner, Barbara A. J.; Hedgeland, Holly; Ellis, John; Allison, William; Sacchi, Marco; Jenkins, Stephen J.; Hinch, B. J.
Abstract : Molecules are commonly thought of as classical objects obeying Newtonian mechanics. However, in their Communication on page 5085 ff., B. A. J. Lechner et al. describe how the diffusion of pyrrole on a Cu(111) surface is determined by the quantum character of the internal vibrations of the molecule. Bending and torsion modes are found to be responsible for the tripling of the barrier to diffusion through lateral changes in their zero point energies.